Towards an Australian Digital Communications Strategy: Lessons from Cross-Country Case Studies - de Percy, Michael Alexander; Campbell, Leith; Reddy, Nitya (Journal of Telecommunications and the Digital Economy, 2022)
In the early 21st century, governments developed national broadband plans to supply high-speed broadband networks for the emerging digital economy and to enable digital services delivery. Most national broadband plans are now focused on moving to ever faster networks, but there is a growing need to develop national digital communications strategies to focus on the demand-side of the broadband “eco-system”. In this paper, we outline the approaches adopted by the United States, Canada, the United Kingdom, Singapore, and Korea to assist in the development (or renewal) of Australia’s national broadband strategy, or, as we prefer, national digital communications strategy. The paper draws on the lessons learned from the case-study countries and the recent pandemic and considers some theoretical aspects of the broadband ecosystem. We conclude by suggesting a process to re-evaluate Australia’s national digital communications strategy as it rolls forward, and to incorporate recent international trends to develop demand-side policies to enable greater adoption and use of existing broadband infrastructure and digital services.